2018
DOI: 10.1007/s11205-018-2028-7
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Working and Unpaid Overtime in the UK: The Role of Gender, Parental and Occupational Status

Abstract: Recent studies have shown that flexible boundaries between work and family may make employees work harder and longer. Yet most studies were not able to show whether there are differences across different types of flexible working arrangements, and whether this relationship may only hold for certain groups of workers. We examine how three different types of flexible working arrangements, that is schedule control, flexitime, and teleworking, are associated with an increase in unpaid overtime hours of workers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 62 publications
2
87
0
Order By: Relevance
“…In fact, recent studies have shown that flexible working increases work intensity, working hours, and overtime [34,35]. This type of control over one's work could have also been given to workers alongside other responsibility, and possibly increased workload as well [36]. We also found a significant difference in perceived job autonomy in that it increased after the transition to open work spaces including ABW.…”
Section: Differences In Job Demands and Job Resources After The Transmentioning
confidence: 49%
“…In fact, recent studies have shown that flexible working increases work intensity, working hours, and overtime [34,35]. This type of control over one's work could have also been given to workers alongside other responsibility, and possibly increased workload as well [36]. We also found a significant difference in perceived job autonomy in that it increased after the transition to open work spaces including ABW.…”
Section: Differences In Job Demands and Job Resources After The Transmentioning
confidence: 49%
“…Fathers are most likely to use flexitime and telework, i.e. arrangements that predominantly give workers more control over their work, possibly for performance enhancing purposes (Lott and Chung 2016;Lott 2018;Chung and Van der Horst 2018a). On the other hand, women, especially mothers were more likely to take up part-time work and other working time reducing arrangements (such as job sharing, temporary reduction of working hours, term-time only), which is the most important factor explaining why workers experience negative career outcomes when working flexibly.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In line with this, existing research refers to the 'flexibilitystigma,' whereby employees who use flexible work arrangements are perceived to be less committed to their work (e.g. Chung & van der Horst, 2018;Konrad & Yang, 2012;Williams et al, 2013). Almer et al (2004) showed in a vignette experiment that employees who used flexible work arrangements such as telework were viewed as being less likely to advance.…”
Section: Introductionmentioning
confidence: 99%